STUDYING THE APPLICATION OF CAD/CAM/CAE SYSTEMS IN THE DESIGN OF COMPONENTS FOR PERSONAL BALLISTIC PROTECTION EQUIPMENT: STUDYING THE APPLICATION OF CAD/CAM/CAE SYSTEMS IN THE DESIGN OF COMPONENTS FOR PERSONAL BALLISTIC PROTECTION EQUIPMENT - Antonov, Stamen; Ivanova, Mariela (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article presents a study of the possibilities for applying the virtual set of tools for 3D modeling, manipulation, and testing of components that are part of individual ballistic protection equipment.